2018
DOI: 10.1101/279539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KCC2 overexpression prevents the paradoxical seizure-promoting action of somatic inhibition

Abstract: Although cortical interneurons are apparently well-placed to suppress seizures, several recent reports have highlighted a paradoxical role of parvalbumin-positive perisomatic-targeting (PV+) interneurons in ictogenesis. Here, we use an acute in vivo model of focal cortical seizures in awake behaving mice, together with closed-loop optogenetic manipulation of PV+ interneurons, to investigate their function during seizures. We show that photo-depolarization of PV+ interneurons rapidly switches from an anti-ictal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 57 publications
(59 reference statements)
7
44
0
Order By: Relevance
“…However, due to the transient and widespread collapse of the postsynaptic Clgradient in pyramidal neurons, GABAergic interneurons are ineffective at curtailing epileptiform discharges, and in fact drive the generation of these events during SE-like activity. Our data complements recent in vitro and in vivo results, which suggest that various GABAergic interneuronal subtypes may promote the extension of seizures when activated once epileptiform activity has become established (Ellender et al, 2014;Sato et al, 2017;Magloire et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, due to the transient and widespread collapse of the postsynaptic Clgradient in pyramidal neurons, GABAergic interneurons are ineffective at curtailing epileptiform discharges, and in fact drive the generation of these events during SE-like activity. Our data complements recent in vitro and in vivo results, which suggest that various GABAergic interneuronal subtypes may promote the extension of seizures when activated once epileptiform activity has become established (Ellender et al, 2014;Sato et al, 2017;Magloire et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, significant Claccumulation and a temporary excitatory shift in GABAergic signalling has been shown to accompany single seizure-like events in both in vitro (Lamsa and Kaila, 1997;Isomura et al, 2003;Fujiwara-Tsukamoto et al, 2010;Ilie et al, 2012;Ellender et al, 2014) and in vivo (Sato et al, 2017) models. The breakdown of the Clgradient serves to explain the surprising excitatory effects of GABAergic interneuronal subtypes recently observed during in vitro and in vivo seizure events (Ellender et al, 2014;Khoshkhoo et al, 2017;Magloire et al, 2018). This suggests that in circuits where seizures have caused sufficient Clloading, GABAAR mediated synaptic signalling can serve to exacerbate rather than control hyperexcitablity, which has direct relevance for the inhibitory efficacy of benzodiazepines.…”
Section: Introductionmentioning
confidence: 98%
“…CI, confidence interval. activation to an excitatory one (Magloire et al, 2019), consistent with the previous demonstration in organotypic cultures (Ellender et al, 2014). They further showed that this GABAergic switch could be prevented by over-expressing KCC2 artificially (introduced by viral vectors), providing strong support for the hypothesized role of short-term ionic plasticity in ictogenesis (Magloire et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…A cannula (Bilaney Consultants Ltd., UK) was implanted in the same location as the recording electrode for sequential pilocarpine injections. Animals were allowed to recover for 2 weeks before induction of acute seizures by pilocarpine (3.5M in saline) (Magloire et al, 2019) injected 0.5mm below the cannula using a microinjection pump (WPI Ltd., USA), a 5 µl…”
Section: Rnamentioning
confidence: 99%
“…We complemented the chronic epilepsy study by looking at the effect of Kcna1-dCas9A treatment on acute seizures evoked by a different mechanism, focal pilocarpine injection in the visual cortex before and after doxycycline administration (Lieb et al, 2018;Magloire et al, 2019). We did not observe robust differences in EEG coastline and power in different frequency bands recorded for 1 hour after pilocarpine in either group, although there was a non-significant trend for Kcna1-dCas9 animals to show an attenuation in seizure severity ( Supplementary Figure 8).…”
Section: Kcna1-dcas9a Decreases Seizure Frequency In a Mouse Model Ofmentioning
confidence: 99%